The Role of the Media in Revealing Corruption Cases - Rahmayanti, Rahmayanti; Pohan, Masitah (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
The mass media plays a strategic role in overseeing government operations and informing the public, particularly in the context of uncovering corruption cases. This study aims to analyze the media's role in uncovering and shaping public opinion regarding corruption cases in Indonesia. Through a qualitative approach using case studies of several media reports related to major corruption cases, it was found that the media acts as a social watchdog, a driver of public opinion, and a catalyst for law enforcement action. However, the media also faces challenges such as interference from political interests and limited access to information. The study's findings indicate that the existence of free and independent media is crucial for strengthening transparency and public accountability. Therefore, strengthening journalistic professionalism and ethics is key to increasing the effectiveness of the media's role in eradicating corruption.